2014
DOI: 10.3109/09513590.2013.871512
|View full text |Cite
|
Sign up to set email alerts
|

Newborn LpL (Ser447Stop, Asn291Ser) genotypes and the interaction with maternal genotypes influence the risk for different types of preeclampsia: modulating effect on lipid profile and pregnancy outcome

Abstract: The newborn/maternal LpL interaction influences the severity of preeclampsia and modulates the lipid profile particularly in severe preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Most studies analyze a single polymorphism in a candidate gene, while a minority analyzes several genes or multiple polymorphisms in one or more genes. These genes have been selected based on the current understanding of PE pathology [ 11 , 24 ], such as genes involved in endothelial functions and related with blood pressure regulation and key genes involved in the regulation of blood pressure: sVEFGR-1 , TGF-β , Eng , RAS , AGT , ACE , AGTR1 [ 27 , 28 ], and eNOS [ 29 , 30 ]; genes that regulate lipid metabolism and oxidative stress: EPHX1 [ 31 , 32 ], GST , NOX1 , SOD2 [ 18 , 33 ], APOE [ 27 ], LPL [ 34 ], and ROS [ 35 , 36 ]; and thrombophilic genes involved in coagulation: F5 , F2 , and MTHFR [ 27 , 28 , 37 39 ]. As previously described, PE can be caused by genetic factors from both parents, an observation supported by Andraweera et al and Zusterzeel et al, who found that variants present in the father, more precisely in the VEGF , PIGF , and GST1 genes, can double the risk of PE [ 40 , 41 ].…”
Section: Association Studiesmentioning
confidence: 99%
“…Most studies analyze a single polymorphism in a candidate gene, while a minority analyzes several genes or multiple polymorphisms in one or more genes. These genes have been selected based on the current understanding of PE pathology [ 11 , 24 ], such as genes involved in endothelial functions and related with blood pressure regulation and key genes involved in the regulation of blood pressure: sVEFGR-1 , TGF-β , Eng , RAS , AGT , ACE , AGTR1 [ 27 , 28 ], and eNOS [ 29 , 30 ]; genes that regulate lipid metabolism and oxidative stress: EPHX1 [ 31 , 32 ], GST , NOX1 , SOD2 [ 18 , 33 ], APOE [ 27 ], LPL [ 34 ], and ROS [ 35 , 36 ]; and thrombophilic genes involved in coagulation: F5 , F2 , and MTHFR [ 27 , 28 , 37 39 ]. As previously described, PE can be caused by genetic factors from both parents, an observation supported by Andraweera et al and Zusterzeel et al, who found that variants present in the father, more precisely in the VEGF , PIGF , and GST1 genes, can double the risk of PE [ 40 , 41 ].…”
Section: Association Studiesmentioning
confidence: 99%